Towards an Inclusive Media Policy Framework Targeting Adolescents in Egypt - Elgredly, Saja (AUC Knowledge Fountain, 2024)
For years, adolescents have been lost between adulthood and childhood. This is even reflected in the policies that directly affect their lives and well-being. In Egypt, there has hardly been a clear political line on how the media should deal with adolescents. As this age group belongs to childhood, most of the laws and regulations are hardly dedicated to address them despite their different characteristics. Within the Egyptian context, there are children's laws concerned with basic children's rights and other laws that relate to the media. However, we notice a gap in adolescent-friendly laws, policies and regulations, especially in the field of media. This study attempts to answer the question of what is needed to ensure the development of adolescents through media content that targets at them. In order to explore the way forward for a more inclusive media policy targeting adolescents in Egypt, a qualitative approach was taken by engaging media experts and Egyptian adolescents directly through interviews and focus groups. The research revealed a dire need for a holistic approach to developing appropriate adolescent media policies. The main research findings concerned the lack of control over the available content addressing adolescents. The importance of raising awareness was also one of the key findings mentioned by experts, families and interviewed adolescents. The study also found that media content aimed at adolescents lacks values which are essential for this age and that alternative content and/or spaces are ultimately needed. The study calls for creating a framework tailored to young people that focuses more on their needs and offers alternatives to the available content targeting adolescents. This study is a first step towards defining the necessary components for a future adolescent-oriented media policy. It advocates for placing adolescent-centered approaches at the heart of any intervention that relates to their wellbeing.